Aloe vera and the Proliferative Phase of Cutaneous Wound Healing: Status Quo Report on Active Principles, Mechanisms, and Applications - Lee, Zhuang Min; Goh, Bey Hing; Khaw, Kooi Yeong (Planta Medica, 2024)
Aloe vera is commonly used as traditional medicine for cutaneous wound healing. Nonetheless, the wound healing mechanisms of Aloe vera remain unclear. This review aims to provide insight into the molecular mechanisms of Aloe vera in promoting cutaneous wound healing, with particular emphasis on the mechanisms that stimulate cell proliferation and migration. Aloe vera has been shown to upregulate growth factors such as keratinocyte growth factor-1 (KGF-1), transforming growth factor-β (TGF-β), cyclin D1, insulin-like growth factor 1 (IGF-1), vascular endothelial growth factor (VEGF), basic fibroblastic growth factor (bFGF), and microfibril-associated glycoprotein 4 (MFAP4), as well as collagen, fibrillin, elastin, α-smooth muscle actin (α-SMA), integrins, and platelet endothelial cell adhesion molecule 1 (PECAM-1, also known as CD31), while downregulating the expression of matrix metalloproteinases (MMPs). In addition, Aloe vera was also found to upregulate PI3K/Akt and MAPK pathways, as well as the TGF-β signalling pathway via Smad proteins. Furthermore, molecular docking studies revealed that certain chemical constituents of Aloe vera bind to some of the forementioned growth factors or signalling molecules. With regards to current applications, although human clinical trials have reported positive results from using Aloe vera in healing open wounds and burns and alleviating some inflammatory skin diseases, the current commercial uses of Aloe vera remain largely focused on cosmetic products. Thus, greater advances are required to promote the use of Aloe vera products in clinical settings.
Keywords: Aloe vera; Liliaceae; wound healing; mechanism; chemical constituent; industrial use